2014
DOI: 10.1128/aem.00388-14
|View full text |Cite
|
Sign up to set email alerts
|

Biotic Interactions and Sunlight Affect Persistence of Fecal Indicator Bacteria and Microbial Source Tracking Genetic Markers in the Upper Mississippi River

Abstract: The sanitary quality of recreational waters that may be impacted by sewage is assessed by enumerating fecal indicator bacteria (FIB) (Escherichia coli and enterococci); these organisms are found in the gastrointestinal tracts of humans and many other animals, and hence their presence provides no information about the pollution source. Microbial source tracking (MST) methods can discriminate between different pollution sources, providing critical information to water quality managers, but relatively little is k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 66 publications
3
59
0
2
Order By: Relevance
“…Few studies have investigated the effect of indigenous biota on the decay of nucleic acid targets. A recent study comparing the effects of sunlight and indigenous microbiota on the decay of nucleic acid targets (Enterococcus 23S rRNA gene, human-specific Bacteroidales 16S rRNA gene, and general Bacteroidales 16S rRNA gene) showed that sunlight had a significant effect at between 0 and 120 hours and indigenous microbiota had a significant effect after 120 hours (44). This is consistent with the results presented herein and suggests that we might have observed an effect attributable to marine microbiota had our experiments continued past 48 h.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have investigated the effect of indigenous biota on the decay of nucleic acid targets. A recent study comparing the effects of sunlight and indigenous microbiota on the decay of nucleic acid targets (Enterococcus 23S rRNA gene, human-specific Bacteroidales 16S rRNA gene, and general Bacteroidales 16S rRNA gene) showed that sunlight had a significant effect at between 0 and 120 hours and indigenous microbiota had a significant effect after 120 hours (44). This is consistent with the results presented herein and suggests that we might have observed an effect attributable to marine microbiota had our experiments continued past 48 h.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of studies on the effect of sunlight on DNA marker persistence, however, are equivocal (33,42). Several studies have found sunlight to have no effect on genetic marker persistence (33,41,43), while other studies have found that the decay rate depends on the presence of sunlight (33,39,41,44). One study found that sunlight exposure affected the decay of a human-specific Bacteroidales genetic marker (a portion of the 16S rRNA gene) but not a genetic marker (a portion of the 23S rRNA gene) for Enterococcus (33).…”
mentioning
confidence: 99%
“…Presently, the advancement of molecular methods for strain detection and differentiation has led to a better understanding of the fates of, and changes in, microorganism communities in the environment (Kim and Wuertz, 2015;Korajkic et al, 2014). Omar (2010) looked for several gene targets, using PCR to encounter pathogenic and commensal E. coli in sewage effluents, and concluded that PCR has a large potential to be used for the monitoring of water samples for the presence of pathogenic E. coli without the need to culture the organisms.…”
Section: Increasing Methodological Robustness On Assaysmentioning
confidence: 99%
“…Zhang, He, and Yan (2015), using cultivation-independent qPCR quantification of 16S rRNA genes and Next-Generation Sequencing (NGS), were able to analyze a microbial community. Korajkic et al (2014) evaluated the effects of ambient sunlight and biotic interactions on the decay of culture-based Fecal Indicator Bacteria (FIB), and compared them to the application of molecular markers with qPCR using 1) Entero1a to target the Enterococcal 23S rRNA gene; 2) GenBac3 to target the Bacteroidales 16S rRNA gene; 3) HF183 to target the Human-associated Bacteroidales 16S rRNA gene; and 4) HumM2 to target the Bacteroidales-like putative σ factor. These authors concluded that there was a strong correlation between molecular FIB and humanassociated genetic markers, but no correlation between any molecular markers and cultured FIB.…”
Section: Increasing Methodological Robustness On Assaysmentioning
confidence: 99%
See 1 more Smart Citation